2016
DOI: 10.1038/jhg.2016.96
|View full text |Cite
|
Sign up to set email alerts
|

A survey on awareness of genetic counseling for non-invasive prenatal testing: the first year experience in Japan

Abstract: The purpose of this study is to summarize the results from a survey on awareness of genetic counseling for pregnant women who wish to receive non-invasive prenatal testing (NIPT) in Japan. As a component of a clinical study by the Japan NIPT Consortium, genetic counseling was conducted for women who wished to receive NIPT, and a questionnaire concerning both NIPT and genetic counseling was given twice: once after pre-test counseling and again when test results were reported. The responses of 7292 women were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…The results after 1 year of genetic counseling in Japan, obtained from surveys on the awareness of genetic counseling for pregnant women, have been summarized and reported . Genetic counseling was conducted before and after NIPT, and a survey was conducted for these sessions.…”
Section: Genetic Counseling and Nipt In Japanmentioning
confidence: 99%
See 1 more Smart Citation
“…The results after 1 year of genetic counseling in Japan, obtained from surveys on the awareness of genetic counseling for pregnant women, have been summarized and reported . Genetic counseling was conducted before and after NIPT, and a survey was conducted for these sessions.…”
Section: Genetic Counseling and Nipt In Japanmentioning
confidence: 99%
“…The results after 1 year of genetic counseling in Japan, obtained from surveys on the awareness of genetic counseling for pregnant women, have been summarized and reported. 32 Genetic counseling was conducted before and after NIPT, and a survey was conducted for these sessions. A total of 7292 people were analyzed, and 94% of the pregnant women surveyed expressed a high degree of satisfaction with the genetic counseling they experienced.…”
Section: Three-year Investigation Of Nipt In Japanmentioning
confidence: 99%
“…The survey was in two parts: (i) pre-and immediately after the NIPT test, from April 2013 to March 2014 and (ii) a year-after the NIPT test, from April 2014 to March 2015. We have already reported on part (i) [11], and the present study is for part (ii). A yearafter research was conducted by a mail-in survey to determine whether the assessment of the NIPT and genetic counseling was changed after the test and one year after.…”
Section: Research Proceduresmentioning
confidence: 83%
“…Because the responses in the first year after the questionnaire were anonymous, and it was impossible to obtain the background data, the personal background of the respondents was unknown; however, the available necessary background information of the respondents who underwent NIPT was shown in the previous study [11] of 7740 women, whereas the present study was limited to those who received negative NIPT results among the 7740 women, and therefore, the background data were not same.…”
Section: Participantsmentioning
confidence: 85%
“…The results from 7292 respondents were reported. 56 Genetic counseling was provided before testing and upon reporting the test results and was conducted by a clinical geneticist or a certified genetic counselor specializing in outpatient genetic counseling. A survey assessing the pregnant women's satisfaction in terms of the time spent on genetic counseling regarding NIPT and the amount of information provided, showed that satisfaction increased with time up to, but not including, 20 min, and remained more or less constant over the 20 min mark.…”
Section: Discussionmentioning
confidence: 99%